SOCIAL MEDIA AND ARTIFICIAL INTELLIGENCE (AI) AS TOOLS TO PROMOTE AND ENHANCE SPORT PRACTICES - Dissanayaka Mudiyanselage, Dinkey Nilankani Bandara (Πανεπιστήμιο Πελοποννήσου, 2024)
The integration of social media and artificial intelligence (AI) has significantly transformed various industries, and the realm of sports is no exception. As powerful tools for communication, engagement, and data analysis, social media and AI have the potential to revolutionize how sports are promoted and practiced. Social media platforms enable athletes, coaches, sports administrators and sports organizations to connect with fans, share content, and build communities, while AI technologies enhance sports practices through advanced analytics, personalized training programs, and performance optimization. By analyzing the individual and combined impacts of these technologies, this research provides a comprehensive understanding of their roles in enhancing engagement, participation, and performance in sports. Using a mixed-methods approach, including qualitative techniques such as in-depth interviews and focus groups, alongside quantitative methods like surveys and social media analytics, the study captures rich qualitative data and quantifies patterns. Findings indicate that social media acts as a virtual hub, boosting participation and fostering community, while AI optimizes training and prevents injuries through player tracking and performance analysis. The synergy between social media and AI allows for tailored content strategies and meaningful fan engagement, creating dynamic sports ecosystems. The significance of this research lies in its potential to revolutionize sports promotion and engagement. By leveraging AI to analyze user data and tailor content, sports organizations can engage diverse audiences and enhance athlete performance. Emphasizing ethical considerations, transparency, and inclusivity is crucial to fostering a vibrant and connected sporting community. This interdisciplinary study highlights the profound impact of social media and AI on the evolving landscape of sports in the digital age.
Keywords: Ηλεκτρονικά κοινωνικά δίκτυα; Τεχνητή νοημοσύνη; Μέσα κοινωνικής δικτύωσης; Μέσα κοινωνικής δικτύωσης - Μάρκετινγκ; Επικοινωνία στον αθλητισμό; Τεχνολογία της πληροφορίας; Μέσα κοινωνικής δικτύωσης στον αθλητισμό; Online social networks; Artificial intelligence; Social media; Social media - Marketing; Communication in sports; Information technology; Social media in sports; Social media; Artificial intelligence (AI); Sports industry; Performance optimization